Influence of chronic stress and oclusal interference on masseter muscle pain in rat - Simonić Kocijan, Sunčana (Array, 2009)
Abstract: This study aimed to investigate the individual effects of chronic stress and occlusal interference, as well as their combined influence on masseter muscle pain. Experiments were performed on 28 male Wistar rats. Animals were submitted to chronic stress procedure, exposed to occlusal interference, or exposed to both mantioned procedures. At the end of the procedure animals were submitted to orofacial formalin test, and nociceptive behavioral response was evaluated. Statisticaly significant diference of nociceptive behavioral response in chronicaly stressed rats and in the animals with occlusal interference in comparation to the control group were not obtained (p>0.05). In contrast, nociceptive behavioral response was significantly increased in rats submitted to both of experimental procedures (p<0.01). These findings suggest that only combination of occlusal interference and chronic stress influence masseter muscle pain